2003
DOI: 10.1590/s1516-35982003000200026
|View full text |Cite
|
Sign up to set email alerts
|

Somatotropina bovina recombinante (rBST) sobre o desempenho e a digestibilidade aparente de novilhas (½ Nelore x ½ Red Angus) em confinamento

Abstract: RESUMO -O objetivo deste trabalho foi avaliar o efeito da somatotropina bovina recombinante (rBST -análogo do BST, obtido comercialmente pela técnica do DNA recombinante), sobre ganho médio diário (GMD), ingestão de matéria seca (IMS), matéria orgânica (IMO), energia metabolizável (IEM) e fibra em detergente neutro (IFDN), ingestão de matéria seca em relação ao peso vivo (IMS/PV), conversão alimentar (CA), rendimento de carcaça (RC) e digestibilidade aparente da matéria seca (DAMS), matéria orgânica (DAMO), pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
3
0
1
Order By: Relevance
“…The average carcass dressing was 51.8%. A carcass dressing of about 52% can be considered normal for heifers slaughtered at 24 months, as observed in other studies of heifers slaughtered of a similar weight (Kazama et al, 2008;Marques et al, 2010;Nascimento et al, 2003).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…The average carcass dressing was 51.8%. A carcass dressing of about 52% can be considered normal for heifers slaughtered at 24 months, as observed in other studies of heifers slaughtered of a similar weight (Kazama et al, 2008;Marques et al, 2010;Nascimento et al, 2003).…”
Section: Resultssupporting
confidence: 54%
“…-June, 2015 crossbreeding and finished in a feedlot can be superior to 1.50 kg day -1 (Macedo et al, 2007;Marques et al, 2000). The feed efficiency of heifers finished in a feedlot may vary from between 6 and 8 kg of dry matter for a gain of 1 kg of body weight, which is close to the observed efficiency of males finished in feedlot (Farias et al, 2012;Marques et al, 2000;Nascimento et al, 2003). In addition, heifers have a better quality of meat compared to the steers and bulls finished on pasture or feedlot (Kazama et al, 2008;Macedo et al, 2007;Rotta et al, 2009) due to their increased sexual precocity.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Additionally, these authors reported a significant decrease in urinary nitrogen excretion, which was not observed in our study. Likewise, Nascimento et al [ 50 ] did not observe differences in nutrient intake. Still, heifers receiving bST injections every 14 days had greater crude protein and organic matter apparent digestibility than control or single-dose treatment.…”
Section: Discussionmentioning
confidence: 91%
“…MATOS (1998) relata em sua pesquisa que nenhum aumento da incidência de mastite e debilidade dos animais foi observado diferindo. Resultados semelhantes em bovinos foram observados por (Nascimento et al 2003) ao avaliarem ganho de peso, conversão alimentar e rendimento de carcaça de novilhas mestiças de Nelore e Red Angus tratadas tanto com dose única de 250 mg de rBST quanto tratadas quinzenalmente.…”
Section: Discussionunclassified